Cellulose Carbamate Polymer
A method for producing cellulose carbamate polymers with controlled molecular weight distribution and improved tensile strength addresses inefficiencies in recycling cellulose-based fibers, enabling high-quality fiber and film production from waste textiles while reducing environmental impact.
Patent Information
- Application Number
- JP2024534571
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-07
- Filing Date
- 2023-01-05
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for recycling cellulose-based fibers are inefficient and environmentally harmful, particularly due to the incineration of used products and the high resource consumption of cotton and polyester, which lack effective processes for producing high-quality cellulose carbamate polymers suitable for spinning and other applications.
A method for producing cellulose carbamate polymers with controlled molecular weight distribution and improved tensile strength by treating cellulose waste with acid and alkaline solutions, followed by ozone bleaching and carbamation, resulting in polymers with specific viscosity and nitrogen content, suitable for wet spinning and molded products.
The method produces cellulose carbamate polymers with improved tensile strength and reduced impurities, enabling the production of high-quality fibers and films from recycled materials, reducing environmental impact by utilizing waste cellulose-based textiles.
Smart Images

Figure 2025501876000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose carbamate polymer. The present invention further relates to a composition comprising particulate cellulose carbamate. The present invention further relates to a coagulated fiber of cellulose carbamate and a coagulated film of cellulose carbamate. A method for determining the presence of a fiber or film of cellulose carbamate in an article is also disclosed. The present invention further relates to a molded article, particularly a molded article comprising cellulose carbamate. [Background technology]
[0002] Currently, most post-consumer textile waste is sent to incineration or landfill, even though around 95% of textile products are recyclable. Only a small proportion of pre-consumer textile products is mechanically recycled. Since the beginning of 2016, the disposal of post-consumer textile products in landfills has been banned in the European Union (EU). In EU countries, textile products and their raw materials that cannot be reused or recycled are therefore typically incinerated in energy-producing plants.
[0003] Naturally, recycling is preferred. The clothing textile market is primarily based on either cotton or polyester, both of which have an impact on the environment. For example, growing cotton requires huge amounts of water as well as pesticides and artificial fertilizers. The global demand for cotton significantly exceeds the Earth's resources for producing virgin material. It is therefore essential to recycle post-consumer textile waste. Processing textile materials to obtain reusable fibers is known, for example WO 2013 / 124265 describes the regeneration of cellulose-containing materials by dispersion and precipitation.
[0004] One process used for recycling cotton-based textile waste materials is described in WO 2018 / 197756, in which the textile materials are treated with an alkaline extraction and then further treated with an acid to cause at least partial dissolution of the cotton-based textile material.
[0005] Another well-known technique used for recycling is the hydrolysis of fibers, which is typically preceded by mechanical removal of metal and hard polymeric pieces such as buttons, zippers, etc. For example, WO 2010 / 124944 discloses a process for the hydrolysis of cellulose.
[0006] The Lyocell process is a process to regenerate cellulose by dissolving cellulosic starting materials with NMMO, a first generation ionic liquid. An extension of the Lyocell process is Ioncell-F, a regeneration process that involves dissolving the starting materials using recently developed ionic liquids as solvents (WO 2014 / 162062). Next, the BioCelSol process utilizes an enzymatic treatment of the starting materials. However, both of these processes focus on making textile products from wood.
[0007] The chemically separated fraction of cellulose fibers can then be used for various purposes, including carbamate formation or spinning.
[0008] A method for producing carbamate cellulose from high-quality virgin cellulose raw materials such as dissolving pulp is known from US Patent No. 7,662,953. US Patent No. 8,066,903 shows a multi-phase dissolution technique for carbamate cellulose, teaching the application of low temperatures for dissolution and the preparation of a solution by first wetting the mass with a dilute alkali of low concentration and then with a highly concentrated and strongly cooled alkali.
[0009] A separation method involving a combination of mechanical and chemical processes for separating cellulose fibers from a textile material containing cellulose fibers and other fibrous and non-fibrous elements is described in EP 3511448. In such a process, the textile material is first chopped to remove larger non-fibrous foreign matter. The remaining fibrous components are then mechanically treated to separate the cellulose fibers from the non-cellulose fibers, which are then subjected to a chemical treatment to remove any non-cellulose fibers still remaining on the cellulose fibers.
[0010] A process for separating cellulosic portions from polyester and cellulose compositions is described in WO 2020 / 013755. The application describes a process for separating cellulosic portions from a feed composition comprising a polyester and a cellulose-containing composition, a cellulosic composition obtainable from a process for separation, a mixture comprising a polyester hydrolysis product obtainable from a process for separation, a pulp, a dissolving pulp, a paper pulp, a regenerated cellulosic fiber product, and a paper product. In the separation process, the polyester / cellulose composition is contacted with a hydrolysis liquid comprising an alkaline solution.
[0011] US Patent No. 4,345,039 discloses a method for recovering polyester fibers from polyester / cotton textile waste, in which the mixed textile is treated with anhydrous HCl gas, which does not damage the polyester but decomposes the cellulosic material into cellulosic powder and produces chlorinated hydrocarbons.
[0012] WO 2021 / 181007 describes a method for separating cellulosic and non-cellulosic fibers from a mixed fibrous textile material containing cellulosic and non-cellulosic fibers. The textile is mechanically disintegrated to open the textile structure, followed by a two-stage acid / alkali chemical treatment. The recovered cellulosic fibers are carbamate-treated. Summary of the Invention
[0013] It is an object of the present invention to overcome at least some of the problems associated with the prior art and provide a cellulose carbamate polymer having improved properties, for example, the cellulose carbamate polymer is suitable for providing a spin dope having a lower degree of polymerization than conventional cellulose carbamates. It is a further object of the present invention to provide a cellulose carbamate having a narrow molecular weight distribution from which fibers having improved tensile strength can be spun.
[0014] The invention is defined by the features of the independent claims. Some particular embodiments are defined in the dependent claims.
[0015] According to a first aspect of the present invention, there is provided a cellulose carbamate polymer having an average intrinsic viscosity of 146-368 ml / g, a nitrogen content of 0.01-3.0 wt.%, a polydispersity index of 2.0-5.0, and a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester of 0.00005-0.5 wt.%.
[0016] According to a second aspect of the present invention, there is provided a composition comprising particulate cellulose carbamate, the cellulose carbamate having an average particle size according to ISO16065-2:2014 of 90 wt% or more of the cellulose carbamate passing through a 260 μm sieve mesh, a proportion of a sieve fraction less than 30 μm being 10 wt% or more, the fibrous fraction consisting of particles having an average particle size with an average fiber length of 1.0 mm or less according to ISO16065-2:2014, an average intrinsic viscosity of 146-368 ml / g, a nitrogen content of 0.01-3.0 wt%, preferably 0.5-2.0 wt%, a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, and a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester of 0.00005-0.5 wt%.
[0017] According to a third aspect of the present invention there is provided a cellulose carbamate coagulated material having an average intrinsic viscosity of 146-368 ml / g, a nitrogen content of up to 2.0% by weight, preferably up to 1.5% by weight, most preferably up to 1.0% by weight, a polydispersity line index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, and a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester, in particular polyethylene terephthalate, of 0.00005-0.1% by weight.
[0018] According to a fourth aspect of the present invention, there is provided a coagulated film of cellulose carbamate having a cellulose solution average intrinsic viscosity of 146-368 ml / g, a nitrogen content of up to 2 wt.%, a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, and a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester, in particular polyethylene terephthalate, of 0.00005-0.1 wt.%.
[0019] According to a fifth aspect of the present invention there is provided a textile garment comprising a yarn, textile, woven or knitted fabric, fabric, woven or knitted fabric comprising textile threads, at least in part comprising cellulose carbamate.
[0020] According to a fifth aspect of the present invention there is provided an article comprising staple fibres, short cut fibres, flock, nonwovens, batting, weaves, tows, flock, filament yarns, tows of filaments, at least in part composed of cellulose carbamate.
[0021] According to a seventh aspect of the present invention there is provided an article comprising a cellulose carbamate polymer having an average intrinsic viscosity of 146-368 ml / g, a nitrogen content of 0.01-3 wt.%, a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, and a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester of 0.00005-0.5 wt.%.
[0022] According to an eighth aspect of the present invention, there is provided an article comprising particulate cellulose carbamate, the cellulose carbamate having an average particle size according to ISO16065-2:2014 of 90 wt% or more of the cellulose carbamate passing through a 260 μm sieve mesh, a sieve fraction of less than 30 μm of 10% or more, and a fibrous fraction consisting of particles having an average particle size of 1.0 mm or less with an average fiber length according to ISO16065-2:2014, an average intrinsic viscosity of 146-368 ml / g, a nitrogen content of 0.01-3.0 wt%, preferably 0.5-2.0 wt%, and a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5.
[0023] According to a ninth aspect of the present invention, there is provided a method for determining the presence of cellulose carbamate by exposing the cellulose carbamate to UV light and detecting fluorescence in the wavelength range of 400 to 520 nm caused by the cellulose carbamate. Also provided is a method for determining the presence of cellulose carbamate, cellulose carbamate fibers or films in an article containing the cellulose carbamate, cellulose carbamate fibers or films, comprising exposing the article to UV light and detecting fluorescence in the wavelength range of 400 to 520 nm caused by the cellulose carbamate, fibers or films.
[0024] According to a tenth aspect of the present invention there is provided the use of cellulose carbamate in an absorbent material, a composite material, a chromatography column, an organic pigment, an adhesive or a microbiologically active stabilizer. [Brief description of the drawings]
[0025] [Figure 1] 1 is a graph showing the decrease in CED viscosity during carbamate formation as a function of time. [Diagram 2] Photograph showing cellulose carbamate, Tencel and viscose fibers (top to bottom) under UV light. [Diagram 3] 1 is an optical microscope photograph showing a knitted cellulose carbamate fabric sample excited with UV light at 365 nm (LP420 filter). [Figure 4] 1 is an optical microscope photograph showing an excited cellulose carbamate knitted fabric sample. [Diagram 5] 1 is an optical micrograph showing a cross section of a knitted cellulose carbamate fabric sample excited with UV light at 365 nm (LP420 filter). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Cellulose carbamates are carbamic acid ester derivatives of cellulose that are insoluble in water and soluble in alkali. The derivatives are obtained by heating urea with cellulose. The polydispersity (PD) is Mw / Mn, where Mw is the weight average molecular weight and Mn is the number average molecular weight, determined by gel permeation chromatography (GPC) / size exclusion chromatography (SEC) equipment.
[0027] When percentages are used, they refer to weight percent of total weight (weight percentage or wt%) unless otherwise indicated.
[0028] Coagulated fibers, films, etc. refer (in this application) to the fully completed end product of the process.
[0029] The nitrogen content in cellulose carbamate refers to the amount of carbamate nitrogen (carbamate group) chemically bonded to cellulose. The nitrogen content (wt%) is measured according to SFS5505:1988. The average intrinsic viscosity ml / g is determined according to ISO5351:2010, and the average is the arithmetic mean. The content of p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyester (wt%) is determined by gas chromatography-mass spectrometry (GC-MS), as described in more detail in the experimental section (Examples 4 and 5).
[0030] As mentioned above, the object of the present invention is to provide a cellulose carbamate polymer having improved properties. The present invention surprisingly provides a cellulose carbamate polymer having a lower degree of polymerization or intrinsic viscosity and a narrower polydispersity index than conventional cellulose carbamates, which is particularly suitable for providing a dope for wet spinning fibers and / or extruding films, and for forming other molded articles.
[0031] According to an exemplary embodiment of the present invention, there is provided a cellulose carbamate polymer having an average intrinsic viscosity of 146-368 ml / g, preferably 161-368 ml / g, suitably 182-267 ml / g, a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, and a nitrogen content of 0.01-3 wt.%. The cellulose carbamate polymer has a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester of 0.00005-0.5 wt.% based on the total weight of the polymer. The p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester are present as residues in the obtained cellulose carbamate polymer due to the presence of polyester-containing textile waste in the raw material. This allows identifying the cellulose carbamate as a material derived at least in part from textile waste. Thus, the material both comprises waste material and has properties suitable for use in the textile industry. This is not usually the case, but rather fibers made from recycled cellulose-based textile waste obtained by carbamateization have not had properties (e.g. strength and low enough linear density) that are good enough to be used in the conventional textile industry, either alone or mixed with other materials.
[0032] Optionally, the cellulose carbamate polymer fluoresces, preferably at a wavelength in the range of 400-520 nm, typically when excited with UV light, preferably having a wavelength of 365 nm.
[0033] Thus, embodiments relate to cellulose carbamate polymers having an average degree of polymerization (DP) of 180 to 500, preferably 200 to 500, especially 230 to 350. The degrees of polymerization correspond to intrinsic viscosities of 146 to 368 ml / g, 161 to 368 ml / g and 182 to 267 ml / g, based on CED viscosity measurements according to ISO 5351:2010. In order to have a cellulose carbamate that is suitable for wet spinning of fibers and / or extrusion of films, as well as for forming other shaped articles, the degree of polymerization of the cellulose carbamate is preferably reduced from conventional values to the range of values described herein.
[0034] The cellulose carbamate according to the embodiment has a nitrogen content of 0.01-3% by weight (measured according to SFS5505:1988 modified as described above), preferably a maximum nitrogen content of 2.5% by weight, suitably in the range of 0.5-2.0% by weight of the cellulose carbamate, more preferably 1.5% by weight. The cellulose carbamate according to the embodiment has a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, measured according to GPC / SEC, and emits fluorescence. The polydispersity index may be modified, for example, by adjusting the temperature, residence time and acid concentration in the acid treatment step, by adjusting the pH and ozone charge in the ozone bleaching and / or decolorizing step, by adjusting the hydrogen peroxide charge, pH and residence time in the hydrogen peroxide bleaching and / or decolorizing step, and / or by adjusting the pH and alkalinity, residence time, urea charge, carbamate temperature and carbamate pressure in the carbamate step. It is believed that ozone in decolorizing colored cellulosic wastes acts on the colorants and color pigments, as well as other coloring components, by oxidation and by achieving primarily the decomposition of the colorants and color pigments, rather than the cellulosic material itself. Therefore, decolorization is preferred over bleaching.
[0035] Indeed, since the sodium salt of terephthalic acid is soluble, it is believed that when the decolorization is carried out under alkaline conditions, the hydrolyzed terephthalic acid remains soluble. This has a positive effect on the washability of the product compared to acid ozonation. In acid ozonation, the hydrolyzed terephthalic acid remaining in the mixture after the alkaline treatment (i.e. not washed out) may precipitate in the fiber during acid ozonation / conventional bleaching. If the decolorization is carried out under alkaline conditions and the following steps are also carried out under alkaline conditions, the terephthalic acid is efficiently washed out of the fiber during the multiple washing stages. This results in a final fiber with a low (less than 0.5 wt%) terephthalic acid content, i.e. a fiber with fewer impurities than conventional fibers and therefore a fiber of better quality. A further advantage of carrying out the decolorization only under alkaline conditions is that the cellulose is no longer hydrolyzed, at least to a significant extent (contrary to acid bleaching or decolorization). Thus, the narrow molar mass distribution obtained in the previous steps is not broadened again due to unnecessary hydrolysis of cellulose.
[0036] According to an embodiment, the cellulose carbamate polymer comprises: - mechanical pretreatment by at least grinding or chopping of cellulosic material comprising at least 50 wt. % cellulose-containing waste, which is a textile waste comprising polyester, into elements having fibres of length 25 mm or less; an acid treatment of the mechanically treated cellulosic material; an acid treatment followed by an alkali treatment to at least partially hydrolyze the polyester; decolorization of the treated cellulosic material with ozone under alkaline treatment; a cellulose carbamation step to form cellulose carbamate from the alkali-treated cellulosic material; The polydispersity index of the resulting cellulose carbamate is adjusted to 2.0-5.0 by acid treatment.
[0037] The method indeed allows the production of cellulose carbamate polymers according to the present invention, with properties that make them particularly suitable for the textile industry, using textile wastes containing polyester as raw materials. The method allows the polydispersity index to be adjusted in the acid treatment. The degree of polymerization can then be adjusted in the carbamate step by adjusting at least one of the following: pH, alkalinity, residence time, urea charge, carbamate temperature, and carbamate pressure.
[0038] Elements in this method refer to fragments, fibers, single staple fibers, etc., ie, grinding or shredding (both can be used) can also be used to break down textile waste down to the fiber level.
[0039] In one embodiment, the polydispersity (PD) is adjusted with an acid, for example a mineral or organic acid, or a combination of acids. Sulfuric acid can be used as the acid for adjusting the PD. For optimal molecular weight distribution of the feedstock, it is beneficial that the preparation of the cellulose feedstock includes a PD adjustment by an acid treatment step, or the feedstock is treated with an acid before mixing the cellulose with urea in the carbamate, preferably before the alkaline treatment for at least partial hydrolysis of the polyester. The reduction of the polydispersity index from the conventional values of conventional cellulose carbamates to values in the range of 2.0 to 5.0, preferably 2.0 to 4.0, most preferably 2.0 to 3.5 provides cellulose carbamates, which in turn provide fibers with improved tensile strength. Spun fibers with improved yield tensile strength, typically in the range of 2.0 to 2.9 cN / dtex, can be obtained using cellulose carbamate polymers with narrow molecular weight distributions (lower polydispersity index) combined with lower average intrinsic viscosities, compared to materials with higher average intrinsic viscosities, i.e., broader molecular weight distributions, with the properties disclosed herein. The dissolution of the cellulose carbamate with the optimal average degree of polymerization combined with the optimal polydispersity is improved as a result of the cellulose carbamate dope being more homogeneous. The nitrogen content of the cellulose carbamate can be modified, for example, by adjusting the pH and alkalinity, residence time, urea charge, carbamation temperature and / or carbamation pressure in the carbamation step.
[0040] Fluorescence is the emission of light by a substance that has absorbed light or other electromagnetic radiation. The cellulose carbamate according to the embodiment emits fluorescence. Typically, the light emitted by a fluorescent material has a longer wavelength than the absorbed radiation. The cellulose carbamate according to the embodiment emits blue / turquoise light, for example with a wavelength in the range of 450-490 nm, which is visually observable when the cellulose carbamate is exposed to UV light, particularly UV light with a wavelength of 365 nm. The fluorescence emission wavelength depends on the excitation wavelength. The cellulose carbamate according to the embodiment emits fluorescence with a wavelength in the range of 400-520 nm (blue), particularly when excited with 365 nm UV light, and with a wavelength in the range of 600-750 nm (red) when excited with 546 nm.
[0041] The cellulose carbamate has a p-terephthalate content of 0.00005-0.5% by weight, in particular less than 0.2% by weight, preferably less than 0.1% by weight. In one embodiment, p-terephthalate is present in the form of acid (p-terephthalic acid) and / or anion (p-terephthalate) and / or unhydrolyzed or partially unhydrolyzed polyester such as polyethylene terephthalate (PET). Partially unhydrolyzed polyester here means that up to 50% of the alkoxy groups are not hydrolyzed. The hydrolyzed polyester is completely decomposed to terephthalic acid, and the intermediate is partially hydrolyzed (i.e. partially unhydrolyzed). When 50% of the bonds in the polyester molecule are broken, the material is in the form of oligomers. The amount of p-terephthalate and / or unhydrolyzed PES present in the cellulose carbamate is related to the purity of the cellulose used in the preparation of the cellulose carbamate. For example, if the raw material comes from a polycotton blend, p-terephthalate is an impurity resulting from the hydrolysis of the polyester. When polycotton is used at least partially as the raw material for the cellulose carbamate polymer, residues of PES or its hydrolysis products may be found in the cellulose carbamate. The polycotton raw material may be subjected to an alkaline treatment step, in which case the polyester may be at least partially hydrolyzed.
[0042] The residues of PES and its hydrolysis products may be separated and measured by chromatography, for example by gas chromatography coupled with a mass spectrometer.
[0043] Cellulose carbamate may contain other impurities depending on the source of raw material. Cellulose carbamate derived from polycotton may contain traces of synthetic fibers other than polyester, such as nylon fibers, polyethylene fibers, elastane fibers, acrylic fibers, modacrylic fibers, chlorofibers, and traces of non-fibrous polymers, such as natural rubber and synthetic polyisoprene, and may contain various nitrogen-containing impurities, such as urea and biuret. The particulate cellulose carbamate is washed until it is at least partially free of water-soluble substances, including nitrogen-based water-soluble substances, and the content of water-insoluble substances in the dried cellulose carbamate is more than 98% by weight of the (washed and dehydrated / dried) particulate cellulose carbamate, suitably more than 99.5% by weight of the (washed and dehydrated / dried) particulate cellulose carbamate. In one embodiment, the cellulose carbamate has a biuret concentration of less than 0.3% by weight of the dried cellulose carbamate. It has been found that by controlling the total amount of water-soluble substances, the biuret concentration can be maintained at a level of less than 0.3% by weight of the (washed and dehydrated / dried) particulate cellulose carbamate.It has further been found that the cellulose carbamate having a biuret concentration of less than 0.3% is particularly suitable for use in the preparation of cellulose carbamate dope.The cellulose carbamate dope may be used, for example, for wet spinning of fibers and / or for extrusion of films, as well as for the formation of other molded articles, such as the creation of sponges and / or foams.
[0044] Nitrogen is present in the cellulose carbamate as a component of the carbamate anion. As mentioned above, by limiting the amount of nitrogen present in the cellulose carbamate, i.e., by adapting the carbamate formation process, the cellulose carbamate can be tailored for a specific use, for example, in one embodiment, the cellulose carbamate has a maximum nitrogen content of 2.0% by weight of the cellulose carbamate, which is particularly suitable for the alkaline wet spinning process. In a further embodiment, the cellulose carbamate has a maximum nitrogen content of 1.5% by weight of the cellulose carbamate, which is preferred for the acid wet spinning process. The nitrogen content of the cellulose carbamate is preferably 0.5-2.0% by weight.
[0045] In a further embodiment, the cellulose carbamate polymer has a number average molecular weight (Mn) of 80,000 g / mol or less, preferably in the range of 30,000 to 80,000 g / mol or less, suitably 30,000 to 60,000 g / mol. The cellulose carbamate polymers having such number average molecular weight are suitable for providing films, fibers and filaments suitable for use in textile and nonwoven products, such as fabrics, clothing or upholstery, such as curtains, drapes, tablecloths, towels, bathroom accessories, carpets, rugs and upholstery. The cellulose carbamate polymers, films, fibers and filaments having a number average molecular weight (Mn) of 80,000 g / mol or less, as well as articles made therefrom and articles containing such films, fibers and filaments, fluoresce at wavelengths of 400 to 520 nm when subjected to excitation. The fluorescence of cellulose carbamate may be due to the presence of nitrogen in the product embodiments, however, this is just one possibility and the scope of the invention is not limited to this explanation.
[0046] A further embodiment relates to a composition comprising particulate cellulose carbamate. In one embodiment, the cellulose carbamate of the composition is composed of particles having an average particle size according to ISO16065-2:2014, in which 90 wt% or more of the cellulose carbamate passes through a 260 μm sieve mesh, the proportion of the sieve fraction less than 30 μm is 10 wt% or more, the fibrous fraction has an average fiber length of 1.0 mm or less according to ISO16065-2:2014, an average intrinsic viscosity of 146-368 ml / g, preferably 161-368 ml / g, suitably 182-267 ml / g, a nitrogen content of 0.01-3.0 wt%, preferably 0.5-2.0 wt%, and a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5. The composition optionally fluoresces, preferably at a wavelength in the range of 400-520 nm, typically when excited with UV light, preferably having a wavelength of 365 nm.
[0047] In a further embodiment, the cellulose carbamate of the composition has a number average molecular weight (Mn) of 80,000 g / mol or less, preferably in the range of 30,000 to 80,000 g / mol or less, suitably in the range of 30,000 to 60,000 g / mol. The number average molecular weight is directly related to the polydispersity index, and therefore both can be adjusted during carbamate formation or during process steps related to pretreatment before carbamate formation to provide carbamates with desired properties. The particle size distribution of the cellulose carbamate composition was also determined by a particle analyzer; that is, 90 wt% of the particles had a particle size of less than 206 μm, 98 wt% had a particle size of less than 500 μm, and the D50 value was 73 μm. Furthermore, the fiber length of the cellulose carbamate fibers in the cellulose carbamate composition was also measured by a fiber image analyzer. The weight fibre length according to ISO16065-2:2014 (pulp - determination of fibre length by automated optical analysis) is less than or equal to 1.0 mm, typically in the range of 0.1 to 0.9 mm, suitably 0.2 to 0.8 mm, preferably 0.5 to 0.7 mm.
[0048] The cellulose carbamate exhibits a content of 0.00005-0.5% by weight, in particular 0.0001-0.1% by weight, of p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyethylene terephthalate. As mentioned above, the amount of p-terephthalate provides an indication of the purity of the cellulose used to prepare the cellulose carbamate. The presence of p-terephthalate also indicates that the cellulose for carbamate originates from a polycotton blend.
[0049] In an embodiment, the composition comprises at least 20% by weight, preferably 40-60% or more by weight, most preferably 90-100% by weight of the dry solid composition. Typically, cellulose carbamate (as an intermediate for an integrated dissolution / spinning process) may contain free water. That is, cellulose carbamate dehydrated, for example, by a press, preferably contains 40-60% or more cellulose carbamate (and less than 60% water), and dried cellulose carbamate preferably contains more than 90% cellulose carbamate and less than 10% water. All percentages are by weight.
[0050] In an embodiment, the composition comprises 98-100 wt.% cellulose carbamate, calculated from the water insoluble solid dry matter, preferably the composition comprises more than 98 wt.% cellulose carbamate, preferably more than 99 wt.% cellulose carbamate, suitably more than 99.5 wt.% cellulose carbamate.
[0051] In a preferred embodiment, the composition is produced by carbamate of cellulosic material obtained from a raw material that at least partially comprises mixed cellulosic textile waste, such as cotton, e.g. polycotton. In the present context, "polycotton" refers to a blend of cotton and polyester fibers. The ratio between cotton and polyester fibers can vary over a wide range, typically 30-99% by weight, in particular 80-98% by weight, of the fibers being cotton and the remaining part being polyester fibers, although the polyester blend may also contain small amounts (typically less than about 5% by weight) of other fibers and / or non-fibrous particles, such as synthetic fibers, including elastane. An embodiment of the present method can additionally be carried out using cellulose carbamate derived from virgin or conventional chemical or dissolving pulps prepared from wood or non-wood fibers, or from natural plant fibers themselves in or in the form of chemical or dissolving pulps, or from mixtures containing other recycled cellulosic materials, such as cardboard or paper.
[0052] Chemical or dissolving pulp was prepared from wood species such as pine, spruce, birch, beech, aspen, maple, larch, acacia, eucalyptus, hemlock, chupelo, and / or oak, or non-wood such as stem fibers (wheat straw, rice straw, barley straw, bamboo, bagasse, and / or reed). The origin of the raw material may be either chemical or dissolving pulp in virgin form or recycled raw materials such as recycled paper and / or cardboard containing chemical or dissolving pulp.
[0053] Natural plant fibers, either as is or in the form of chemical pulp or dissolving pulp, are also useful as raw material sources. The origin of natural plant fibers may be either their virgin form, natural plant fiber-containing textile products, or recycled natural fiber-containing textile products. Natural plant fibers include seed fibers such as cotton and kapok, bast fibers such as hemp, jute, kenaf, ramie, abaca, and linen, leaf fibers such as abaca, sisal, pineapple, and banana, and fruit fibers such as coir.
[0054] Thus, in one embodiment, recycled fibrous feedstock is used as a feedstock for producing cellulose carbamate.
[0055] The particle size affects the suitability of the composition for various applications. In one embodiment, the composition is composed of particles having an average particle size in which 90 wt% or more of the cellulose carbamate passes through a 260 μm sieve mesh, the percentage of the sieve fraction less than 30 μm is 10 wt% or more, and the fibrous fraction has an average fiber length of 1.0 mm or less according to ISO16065-2:2014, typically 0.1 to 0.9 mm, suitably 0.2 to 0.8 mm, preferably 0.5 to 0.7 mm. Cellulose carbamate is an inherently fibrous material. Thus, the fibers of cellulose carbamate obtained by grinding the particulate cellulose carbamate typically have a fiber length of about one tenth of the fiber length of recycled polycotton raw material. In one embodiment, the chemical treatment step and the mechanical step prior to carbamate comprises the recycled polycotton feedstock being crushed and / or shredded until it comprises fragments having fibres with a fibre length of 25mm or less, preferably 10mm or less, suitably 1-7mm, most suitably 5-7mm. The crushing step of the cellulose carbamate process comprises the use of high shear mixing during mixing of the high concentration of cellulose and urea prior to crushing of the carbamate cellulose before or after the carbamate step and washing step. Suitable equipment for mechanical treatment are for example knife mills, hammer mills, ball mills, disc mills, pin mills, counter rotating equipment, sieve press equipment and extruders. In one embodiment, the suitable equipment for high shear mixing of the cellulose and urea is a pellet press, and the mechanical treatment may be carried out by using one or more pellet presses in series. In one embodiment, the cellulose carbamate has a fibre length of 1mm or less, typically in the range of 0.1-0.9mm, suitably 0.2-0.8mm, preferably 0.5-0.7mm.
[0056] In an embodiment, the composition has a viscosity of 250 kg / m 3 ~800kg / m 3 , preferably 300 to 500 kg / 3The bulk density ranges from 0.01 to 0.01. The bulk density is an important composition characteristic when considering product handling, processing, storage and transportation. The final composition should not be fluffy or loose, and a higher bulk density is preferred. The bulk density of the composition is adjusted by adjusting the degree of polymerization or viscosity and the polydispersity index of the cellulose carbamate. The bulk density may be affected by the grinding step during the carbamate process. The final product is compressible during packaging if not directly used for dissolving or preparing molded articles. The degree of polymerization or viscosity and the polydispersity index are adjusted as described above. The bulk density of the composition is increased by decreasing the degree of polymerization and narrowing the polydispersity index.
[0057] An embodiment relates to coagulated fibers of cellulose carbamate. In one embodiment, the coagulated fibers of cellulose carbamate comprise cellulose carbamate having an intrinsic viscosity of 146-368 ml / g, preferably 161-368 ml / g, suitably 182-267 ml / g, a nitrogen content of up to 3% by weight of the cellulose carbamate, a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyethylene terephthalate (PES) of 0.00005-0.1% by weight, and optionally fluoresce, preferably fluoresce when excited with UV light having a wavelength in the range of 400-520 nm, typically 365 nm.
[0058] In a particular embodiment, the fibers comprise cellulose carbamate exhibiting a number average molecular weight (Mn) of 80,000 g / mol or less, preferably in the range of 30,000 to 80,000 g / mol or less, suitably in the range of 30,000 to 60,000 g / mol.
[0059] In a suitable embodiment, the fibers are obtained by spinning cellulose carbamate having a nitrogen content of 0.1-2%, preferably 0.2-1.0%, by weight of the cellulose carbamate in an acidic spin bath to form fibers, and recovering the fibers.
[0060] In another embodiment, the fibers are obtained by spinning cellulose carbamate having a nitrogen content of 0.3 to 3 wt. %, preferably 0.5 to 2.2 wt. %, especially 0.7 to 1.8 wt. %, in an alkaline spin bath to form fibers, and recovering the fibers.
[0061] In a further embodiment, the fiber is obtained by providing a composition according to any of the above-mentioned embodiments of the composition, forming a dope of the composition, coagulating the fiber by a wet spinning process in an acidic spin bath to form a fiber, recovering the fiber from the spin bath, and drawing the fiber under acidic conditions.
[0062] In yet another embodiment, the fiber is obtained by providing a composition according to any of the above-mentioned embodiments of the composition, forming a dope of the composition, coagulating the fiber by a wet spinning process in an alkaline spin bath to form a fiber, recovering the fiber from the spin bath, and drawing the fiber under alkaline conditions.
[0063] The dope may be cellulose carbamate dissolved in an ionic liquid for the process of coagulation or regeneration by dry jet wet spinning, where the cellulose carbamate is extruded and the dope is drawn across an air gap into water. The ionic liquid may be an organic compound developed for the direct dissolution of cellulose. Preferably, the ionic liquid may be 4-methylmorpholine 4-oxide (NMMO). In a further embodiment, the cellulose carbamate has a maximum nitrogen content of 3.0% by weight of the cellulose carbamate for dry jet wet spinning.
[0064] In other embodiments, the cellulose carbamate dope may be mixed with a viscose dope (a cellulose solution prepared by the viscose process) and the mixture is subjected to wet spinning to obtain coagulated fibers of cellulose carbamate.
[0065] The carbamate group is stable under weakly alkaline conditions, for example air-dried cellulose carbamate in the form of a fibrous powder, i.e., particulate form. The composition containing particulate cellulose carbamate is alkaline with a pH of 10 or less, preferably 9.0 or less. The pH is determined by suspending 10 g of dry cellulose carbamate in 90 g of water, leaving it at 20 degrees Celsius for 30 minutes, and then measuring the pH of the decanted aqueous solution.
[0066] Carbamate groups are stable under neutral or alkaline conditions (e.g., under acidic spinning and drawing conditions). Carbamate groups are hydrolyzed under concentrated alkaline conditions (e.g., dissolved cellulose carbamate is hydrolyzed in an aqueous alkaline solution with a NaOH content of at least, e.g., 6.5% by weight of the dope). Cellulose carbamate starts hydrolysis instantly after dissolving under alkaline conditions to produce the dope. The higher the temperature of the dope and the longer the time from dissolution to coagulation, the higher the rate of hydrolysis and the lower the amount of carbamate groups bound to cellulose, i.e., the lower the nitrogen content bound to cellulose. The rate of hydrolysis determines the degree of substitution of cellulose carbamate. Different spin baths, e.g., alkaline spin baths and acidic spin baths in the wet spinning process, the subsequent drawing step, the further washing process and the further post-treatment process, can be used to produce fibers with preferred or more suitable properties.
[0067] Optionally, the filaments are cut into fibres, thereby obtaining staple filaments or fibres of cellulose carbamate, in particular staple fibres or short cuts.
[0068] The post-treatment process may optionally include one or more of the following process steps: a) post-hydrolysis of carbamate groups with hot alkaline solution (e.g., cellulose carbamate fiber with 0.8% nitrogen inductance, coagulated in alkaline coagulation bath and stretched in alkaline stretching, was subjected to post-hydrolysis in post-treatment by treating the fiber with post-hydrolysis solution containing Na2CO3 and NaOH at 95 degrees Celsius for 3 minutes, and the nitrogen content of the recovered fiber was 0.17 wt%), b) acid bleaching step and / or neutral bleaching step and / or alkaline bleaching step, and c) spin finishing. Thus, fiber properties can be manipulated during coagulation, stretching, further washing and / or further post-treatment depending on the alkalinity, temperature and residence time in each step, and such post-treatment can be selected to adjust the hydrolysis rate of cellulose carbamate in particular.
[0069] The shape of the fiber can be modified by adjusting the degree of substitution of the cellulose carbamate that goes into spinning and drawing, for example, rounded oval, bean or leaf-shaped fibers can be obtained as a result of the controlled spinning and drawing of nitrogen-containing cellulose carbamate, and a smooth surface can be formed.
[0070] According to one embodiment, there is provided a method for producing cellulose carbamate filaments or fibers, the method comprising the steps of providing a cellulose carbamate dope comprising cellulose carbamate dissolved in an aqueous sodium hydroxide solution, the cellulose carbamate dope exhibiting dissolved zinc compounds, and feeding the dope into a coagulation unit.
[0071] According to one specific embodiment, the aqueous alkali cellulose carbamate dope comprises: 6 to 10 wt %, preferably 8 to 10 wt %, of cellulose carbamate (CCA); 5 to 10 wt%, preferably 5 to 7 wt%, of sodium hydroxide (NaOH); 0.08 to 1.6 wt. %, preferably 0.08 to 1.2 wt. % zinc; The weight percentage (wt%) is calculated from the total weight of the cellulose carbamate dope. When zinc oxide (ZnO) is used, the amount is 0.1-2 wt%, preferably 0.1-1.5 wt%. Other zinc compounds such as sodium zincate can also be used. In fact, cellulose carbamate is soluble in an aqueous alkaline solution consisting of sodium hydroxide and zinc oxide, or zinc hydroxide in a sodium hydroxide solution. The addition of zinc has been shown to improve the solubility of cellulose carbamate and improve the stability of the cellulose carbamate solution. In this case, the alkaline solution consists of sodium hydroxide, and zinc oxide and / or zinc hydroxide, which forms a zincate salt. Thus, in an embodiment, the alkaline solution comprises sodium zincate.
[0072] Cellulose carbamate can be dissolved directly in sodium hydroxide, typically at a concentration of 5-10% by weight of the cellulose carbamate dope. The concentration of carbamate in the cellulose carbamate dope has a significant impact on the cost of the process. With low DP and narrow polydispersity, the amount of sodium hydroxide can be reduced and the concentration of CCA in the solution can be increased. Once the cellulose carbamate dissolves (carbamate), hydrolysis begins and some of the carbamate groups hydrolyze during further processing, including dissolution and filtration and degassing of the cellulose carbamate dope. The nitrogen content of the cellulose carbamate can be adjusted by changing the dissolution conditions, such as time, temperature, and / or sodium hydroxide concentration. Low temperatures slow down the hydrolysis, which increases the time that the dissolved CCA can be stored. The optimal nitrogen content for wet spinning or coagulation of cellulose carbamate depends on the coagulation process and the intended application. Hydrolysis of the carbamate stops once coagulation occurs in the acid coagulation bath. In the case of alkaline coagulation bath, hydrolysis of cellulose carbamate also occurs during coagulation and further alkaline drawing steps. In both acid and alkaline spinning, the coagulated and drawn fiber can be subjected to a further alkaline post-treatment step, and alkaline hydrolysis can be continued under controlled conditions. The nitrogen content of the final product can be adjusted in the washing and post-treatment steps, where residual carbamate groups can be mainly removed by the alkaline treatment step.
[0073] According to an embodiment, a solidified film of cellulose carbamate is also provided. In one embodiment, a solidified film of cellulose carbamate is provided having a cellulose solution average intrinsic viscosity of 146-368 ml / g, preferably 161-368 ml / g, suitably 182-267 ml / g, a nitrogen content of up to 2 wt%, a polydispersity index of 2.0-5.0, preferably 2.0-4.0, most preferably 2.0-3.5, and a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyethylene terephthalate (PES) of 0.00005-0.1 wt%. Optionally, the film fluoresces, preferably when excited with a wavelength in the range of 400-520 nm, typically with UV light, preferably with UV light having a wavelength of 365 nm.
[0074] In a further embodiment, the film comprises a cellulose carbamate having a Mn of less than or equal to 80,000 g / mol, preferably from 30,000 to 80,000 g / mol, suitably from 30,000 to 60,000 g / mol.
[0075] In a particular embodiment, the film is obtained by extruding a cellulose carbamate dope in a coagulation bath to form a film.
[0076] Further embodiments relate to articles. In one embodiment, a textile garment is provided that includes a fabric, woven or knit fabric made from fiber threads, at least in part of which is made of cellulose carbamate fiber according to any of the above-mentioned embodiments. In a suitable embodiment, an article is provided that includes a nonwoven sheet, batting and / or weave, at least in part of which is made of cellulose carbamate according to the above-mentioned embodiments.
[0077] In further embodiments, the article is a molded article, such as a sponge or foam. In embodiments, the molded article may be a molded article, such as a composite. The molded article in such embodiments comprises particulate cellulose carbamate and / or cellulose carbamate fibers.
[0078] Surprisingly, the presence of cellulose carbamate fibers or films or particles, in particular cellulose carbamate fibers or films, or particles as mentioned above, can be determined by fluorescence detection. Thus, embodiments provide a method for determining the presence of cellulose carbamate fibers or films in an article that includes such fibers or films.
[0079] In an embodiment, the method comprises exposing the article to UV light, preferably 365 nm UV light, and detecting the fluorescence in the wavelength range of 400-520 nm produced by the cellulose carbamate fibers. In one embodiment, the article is a yarn, a tow of filaments, staple fiber, short cut fiber, flock or film. In a further embodiment, the article is a textile garment comprising such fibers, such as a bleached and / or colored article. In accordance with the above, in an embodiment, the presence of cellulose carbamate in the man-made cellulosic mixture is detectable by detecting the fluorescence when the cellulose carbamate is mixed with viscose, lyocell or modal in a fiber, filament, yarn or fabric, since other regenerated fibers do not fluoresce.
[0080] Some embodiments are illustrated by the following examples.
[0081] Example 1: Chemical pretreatment, carbamate and wet spinning Recycled mixed color sorted cotton textile waste, a polycotton raw material with a CED viscosity of 800 ml / g (ISO5351:2010) containing 4.0 wt% non-cellulosic fibers (mainly polyester but with traces of nylon, isoprene-containing materials (elastic bands), polyethylene / polypropylene), was mechanically shredded to disrupt the fabric structure and form shreds with fibers of average length 6 mm. The shredded material was chemically pre-treated using a two-stage cooking procedure and bleaching / decolorization. In the first acidic stage, the material was treated with sulfuric acid. In the second alkaline stage, the washed acid-treated material was chemically treated with sodium hydroxide to hydrolyze most of the polyester.
[0082] In the first acid stage, the shredded material was treated with sulfuric acid at 95 degrees Celsius for 60 minutes. The consistency of the textile waste was 10 wt% and the initial acid charge was 5.0 g / L. The medium consistency pulp was treated in a continuous plug flow reactor. The pH value of the final wash was 3.2 as measured in the wash filtrate, which corresponds to 0.6 g free sulfuric acid per kg dry acid-treated material. The viscosity of the acid-treated material was 294 ml / g (based on CED viscosity measurement according to ISO5351:2010).
[0083] In the second alkaline stage, the washed acid-treated material was treated with sodium hydroxide in a pressure reactor equipped with a medium consistency pump at 110°C for 120 min. The textile waste concentration was 8.3 wt% and the initial alkaline charge was 72 g / L. The pH of the final wash liquor was 10.0. The viscosity of the chemically pretreated material was 290 ml / g (based on CED viscosity measurement according to ISO5351:2010). The average yield in the alkaline stage was 92 wt% solids on oven-dried material.
[0084] The degree of polymerization was further adjusted in the bleaching stage, which included both ozone and alkaline hydrogen peroxide treatment stages. Ozone treatment in the alkaline range did not significantly reduce the CED viscosity of the material, and in particular the loss in viscosity was less than that obtained with ozone under acidic conditions. Thus, the narrow polydispersity index obtained in the preceding process stages is maintained in the alkaline bleaching stage. The material obtained from the bleaching process was appropriately dehydrated by air flow in a press for the subsequent carbamate process.
[0085] Ozone decolorization was carried out using a medium consistency loop pressure reactor. The loop was first filled with warm soft water and shredded textile (300 g, oven dry) was transferred to the system. Then the feedstock and water slurry were fed into the pressure reactor. NaOH, 20 kg / BDT (oven dry metric ton of feedstock) was fed into the reactor to obtain a textile waste concentration of 8.5 wt% with a pH of 11.8. The pretreated textile waste slurry was heated to 70°C. The estimated ozone concentration fed to the reaction was 16 wt% and the time for feeding was 150 min. The total ozone charge was 4.0 kg / BDT. After the ozone stage, 4.0 m 3 The slurry was cooled by adding 100 ml of water. The cooled and diluted slurry was dewatered in a screw press. The pH of the filtrate was 10.0. The viscosity of the ozone decolorized material was 279 ml / g (ISO5351:2010).
[0086] Next, a peroxide stage was performed on the ozone bleached textile waste. The ozonated material was pumped into the reactor and the consistency of the slurry in the pressure reactor was 8.0 wt%. The reaction mixture was heated to a reaction temperature of 80°C and the ph was adjusted to 11.6 with NaOH. The reaction time of the peroxide stage was 60 minutes and the hydrogen peroxide charge was 5 kg / BDT. The bleached material was washed through a screw press. The consistency of the screw press feed was 2.2 wt% and the thickening factor was 21 for the first washing sequence. For the second washing sequence, the thickening factor was 25. The viscosity of the resulting bleached pulp was 265 ml / g (ISO5351:2010).
[0087] The carbamate process was carried out as described in FI Patent No. 112869, FI Patent No. 112795 and WO 2021 / 038136. In the carbamate stage, the degree of polymerization of cellulose and the polydispersity of the final product were optimized by chemicals, time, grinding and temperature. Figure 1 shows the results of the optimization with respect to time, showing how the CED viscosity (ml / g, y-axis) changed with reaction time (min, x-axis). The bulk density of the final composition was adjusted by grinding. After carbamate of the decolorized sample (mentioned above), the viscosity of the resulting cellulose carbamate was 210 ml / g (ISO 351:2010), corresponding to a DP of 268 and a PD of 3.28. See Table 1.
[0088] The cellulose carbamate obtained from the carbamate formation process is further dissolved to produce cellulose carbamate by wet spinning process. That is, the milled air-dried cellulose carbamate powder is slurried and dissolved in aqueous sodium hydroxide solution containing dissolved zinc oxide to form a cellulose carbamate dope with a zinc oxide content of 1.2 wt%, a sodium hydroxide content of 6.5 wt% and a cellulose carbamate content of 8.5 wt%, with the remainder being water. The cellulose carbamate dope obtained from the dissolution process is then filtered using a two-stage back-flush filtration process, with a 20 μm filter medium in the second filtration stage. The wet spinning of the filtered and degassed cellulose carbamate dope is carried out using an acidic spin bath that is optimal for the cellulose carbamate process, containing sodium sulfate, free sulfuric acid and aluminum sulfate, with a pH value of 0.75, a sodium sulfate to aluminum sulfate ratio of 1.63, a density of 1.300 kg / L and a temperature of 20°C.
[0089] The viscosity of the chemically pretreated materials was measured and the corresponding polydispersity (PD) values are shown in Table 1. Results for cellulose carbamate produced from dissolving pulp without pretreatment to optimize polydispersity were also measured as a comparative example, Carbamate Comparison. CED viscosity measurements to determine DP were according to ISO 5351:2010. Fiber linear density (dtex) and fiber tensile strength (cN / dtex) of staple fibers were measured according to ISO 1973:2021 and ISO 5079:2020, respectively. Dry fibers were conditioned at 65±2% relative humidity and 20±2°C temperature for at least 24 hours. The test speed was 20 mm / min, the gauge length was 20 mm, and the average value of 20 measurements (Favigraph, Textechno) was obtained. The measured stable fiber properties are shown in Table 1.
[0090] [Table 1]
[0091] Mw (g / mol) and Mn (g / mol) were measured from chemically pretreated cellulose carbamate fibers by GPC / SEC (gel permeation chromatography (GPC) / size exclusion chromatography (SEC) instrument), Agilent PL-GPC220 system. Samples were dissolved in LiCl / DMAc (DMAc stands for dimethylacetamide). The method is relative and uses pullulan polysaccharide standards and a Polymer Lab 20 μm mixed A column.
[0092] The average particle size of the cellulose carbamate composition was measured by sieve analysis. Sieves of different mesh sizes were stacked with the largest mesh size on top. The sequence of the sieves from top to bottom was 1400 μm, 800 μm, 261 μm, 160 μm, 100 μm, 71 μm, 45 μm, and 30 μm. The sample was vibrated for 7 minutes. The weight of the aggregates retained on each sieve was measured and expressed as the passing percentage. On average, 93 wt% of the particles passed through the 261 μm sieve mesh and 26 wt% of the particles passed through the less than 30 μm mesh.
[0093] The particle size distribution was also determined by a Malvern Mastersizer 2000: 90 wt% of the particles were smaller than 206 μm, 98 wt% were smaller than 500 μm, with a D50 value of 73 μm. Values corresponded to sieve analysis.
[0094] The effects of the degree of polymerization (DP) and polydispersity of cellulose carbamate on fiber properties were investigated. The cellulose carbamate obtained from the carbamate process was further dissolved to produce cellulose carbamate fibers by wet spinning process. The filament tow obtained from spinning was cut into staple fibers with a cut length of 40 mm. The fiber linear density and broken fiber tensile strength and elongation measured from the staple fibers are listed in Table 1 above.
[0095] It should be noted that narrow polydispersity is beneficial. To draw fibers with sufficient textile fiber quality, i.e., greater than 2.0 dtex, a PD of less than 5.0 was required. The best fiber results were achieved when the DP was less than 300, the PD was less than 4.0, and the Mn was less than 60000 g / mol.
[0096] The degree of polymerization (DP) of the staple fibers was also measured according to ISO 5351:2010. The DP did not change during the wet spinning process, and the DP was at the same level as that of the corresponding cellulose carbamate.
[0097] Example 2 Cellulose carbamate Tencel™ and viscose fibers were irradiated with a UV light source, Analytik Jena, 365 nm. The results are shown in Figure 2. A clear distinction was detected, as the cellulose carbamate fibers fluoresce blue, even though the cellulose carbamate content in the fiber mixture was only 20%.
[0098] Example 3 Cellulose carbamate knitted fabrics consisting of 100% cellulose carbamate were investigated with an optical microscope Zeiss Imager, Z2m and a fluorescence microscope HVP R 120W / 45C VIS 320-500 nm. The samples fluoresced in the wavelength range 400-520 nm (blue) when excited at 365 nm with an LP420 filter; see Figure 3. The samples fluoresced in the wavelength range 600-750 nm (red) when excited at 546 nm with an LP590 filter; see Figure 4. Cross-section samples of the knitted fabrics were also prepared and excited at 365 nm with an LP420 filter; see Figure 5. The cross-sections also fluoresced in the blue.
[0099] Example 4 The content of terephthalic acid in cellulose carbamate fiber produced as described in Example 1 was measured by GC / MS (gas chromatography-mass spectrometry) system. Samples were acidified with hydrochloric acid to pH<3 and dried in an oven overnight. Free terephthalic acid was extracted from the samples with pyridine / methanol solvent and concentrated to 5 ml. The extracted terephthalic acid was methylated and analyzed by GC / MS. The free terephthalic acid content of the samples was calculated against external calibration standards. The amount of terephthalic acid was 5 mg / kg (of cellulose carbamate fiber).
[0100] Example 5 The content of terephthalic acid in the cellulose carbamate polymer produced as described in Example 1 was measured by a GC / MS (gas chromatography-mass spectrometry) system. The sample was first refluxed in sodium hydroxide (10 wt%) for 4 hours to hydrolyze the polyethylene terephthalate in the sample. The terephthalic acid was extracted from the sample, dissolved in pyridine / methanol solvent, and concentrated to 5 ml. The extracted terephthalic acid was methylated and analyzed by GC / MS. The terephthalic acid content was calculated against an external calibration standard. The amount of terephthalic acid was 1078 mg / kg (of the cellulose carbamate polymer).
[0101] It is to be understood that the disclosed embodiments of the invention are not limited to the particular structures, process steps, or materials disclosed herein, but extend to equivalents thereof as would be recognized by one of ordinary skill in the relevant arts, and that the terminology used herein is used only for the purpose of describing particular embodiments, and is not intended to be limiting.
[0102] Reference throughout this specification to an embodiment or embodiments means that the particular feature, structure or characteristic described in connection with the embodiment is included in at least one embodiment of the present invention. Thus, the appearances of the phrases "in one embodiment" or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment. Exact numerical values that refer to numerical values using the terms "such as," "for example," "about," or "approximately" are also disclosed.
[0103] As used herein, a plurality of items, structural elements, compositional elements, and / or materials may be presented in a common list for convenience. However, these lists should be construed as if each member of the list were individually identified as a separate and unique member. Thus, the individual members of such lists should not be construed as de facto equivalents of any other members of the same list solely based on their presentation in a common group, unless otherwise indicated. Also, various embodiments and examples of the present invention may be referred to herein along with alternatives of the various components thereof. It should be understood that such embodiments, examples, and alternatives are not construed as de facto equivalents of each other, but are considered as separate and autonomous representations of the present invention.
[0104] Furthermore, the described features, configurations, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, numerous specific details are provided, such as examples of lengths, widths, shapes, etc., to provide a thorough understanding of embodiments of the invention. However, one of ordinary skill in the art will recognize that the invention can be practiced without one or more of the specific details, or with other methods, components, materials, etc. In other instances, well-known structures, materials, or operations have not been shown or described in detail to avoid obscuring aspects of the invention.
[0105] While the foregoing examples illustrate the principles of the present invention in one or more specific applications, it will be apparent to those skilled in the art that numerous variations in the embodiments, uses and details may be made without the exercise of inventive skill and without departing from the principles and concepts of the present invention. Accordingly, it is not intended that the present invention be limited except as by the scope of the claims which follow.
[0106] In this specification, the verbs "comprise" and "include" are used as open-ended limitations that do not exclude or require the presence of any unrecited features. Features recited in the dependent claims are mutually freely combinable unless expressly stated to the contrary. Furthermore, it is to be understood that the use of "a" or "an", i.e. the singular form, throughout this specification does not exclude the plural form. [Industrial Applicability]
[0107] At least some embodiments of the present invention find industrial application at least in the textile industry. Cellulose carbamate can be used to form high-quality textile fibers from virgin raw materials with recyclable cellulosic materials. In addition to providing high-quality textile fibers, cellulose carbamate has a variety of applications, such as in extruded films, composites, sponges, foams, pigments, adhesives, stabilizers, and, for example, in stationary phases of chromatography columns for use in various analytical methods.
[0108] Abbreviation DP Degree of Polymerization PD polydispersity CCA Cellulose Carbamate PET Poly(ethylene terephthalate)
Claims
1. An average intrinsic viscosity of 146 to 368 ml / g; A nitrogen content of 0.01 to 3% by weight; and a polydispersity index of 2.0 to 5.0; A cellulose carbamate polymer having a content of 0.00005 to 0.5% by weight of p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyester.
2. The cellulose carbamate according to claim 1, having an average intrinsic viscosity of from 161 to 368 ml / g, suitably from 182 to 267 ml / g.
3. The cellulose carbamate according to claim 1 or 2, having a polydispersity index of from 2.0 to 4.0, most preferably from 2.0 to 3.
5.
4. 4. Cellulose carbamate according to any one of claims 1 to 3, exhibiting a content of p-terephthalate and / or p-terephthalic acid and / or unhydrolyzed or partially unhydrolyzed polyester, in particular polyethylene terephthalate, of less than 0.2% by weight, preferably less than 0.1% by weight.
5. The cellulose carbamate according to any one of claims 1 to 4, having a biuret concentration of less than 0.3% by weight.
6. Cellulose carbamate according to any one of claims 1 to 5, having a maximum nitrogen content of 2.5% by weight, suitably in the range of 0.5 to 2.0% by weight, preferably up to 1.5% by weight.
7. The cellulose carbamate polymer according to any one of claims 1 to 6, having a Mn of up to 80,000 g / mol, preferably in the range of from 30,000 g / mol to up to 80,000 g / mol, suitably in the range of from 30,000 to 60,000 g / mol.
8. The cellulose carbamate polymer of any one of claims 1 to 7, which fluoresces in the wavelength range of 400 to 520 nm under excitation from UV light.
9. A composition comprising particulate cellulose carbamate, the cellulose carbamate being composed of particles having an average particle size in which 90 wt % or more of the cellulose carbamate passes through a 260 μm sieve mesh and the proportion of the sieve fraction less than 30 μm is 10 wt % or more, the composition having an average intrinsic viscosity of 146 to 368 ml / g, a nitrogen content of 0.01 to 3 wt %, a polydispersity index of 2.0 to 5.0, and a content of p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyethylene terephthalate of 0.00005 to 0.5 wt %.
10. 10. The composition of claim 9, exhibiting a fibrous fraction having an average fiber length of 1.0 mm or less according to ISO 16065-2:2014.
11. The composition according to any one of claims 9 to 10, wherein the composition is alkaline.
12. 12. The composition according to any one of claims 9 to 11, comprising 98 to 100 wt% cellulose carbamate, preferably more than 98 wt% cellulose carbamate, preferably more than 99 wt% cellulose carbamate, suitably more than 99.5 wt% cellulose carbamate, calculated from the dry solids content.
13. 13. The composition according to any one of claims 9 to 12, having a dry solids content of at least 20 wt%, preferably 40 to 60 wt% or more, most preferably 90 to 100 wt%, calculated from the total weight of the composition.
14. 300 kg / m as measured by ISO 60:1977 3 ~800kg / m 3 , preferably 300 to 500 kg / m 3 The composition of any one of claims 9 to 13, having a bulk density of
15. A composition according to any one of claims 9 to 14, wherein the cellulose carbamate has a Mn of up to 80,000 g / mol, preferably from 30,000 to 80,000 g / mol, suitably from 30,000 to 60,000 g / mol.
16. The composition of any one of claims 9 to 15, which fluoresces at wavelengths in the range of 400 to 520 nm under excitation from UV light.
17. An average intrinsic viscosity of 146 to 368 ml / g; A nitrogen content of up to 2% by weight; and a polydispersity index of 2.0 to 5.0; A cellulose carbamate coagulated material having a content of 0.00005 to 0.1 wt. % p-terephthalate and / or p-terephthalic acid, and / or unhydrolyzed or partially unhydrolyzed polyethylene terephthalate.
18. 20. The solidification material of claim 17 in the form of a fiber or a film.
19. 19. The solidification material according to claim 17 or 18, comprising cellulose carbamate having an average intrinsic viscosity of 161-368 ml / g, suitably 182-267 ml / g, and / or having a polydispersity index of 2.0-4.0, most preferably 2.0-3.5, and / or exhibiting a Mn of up to 80,000 g / mol, preferably 30,000-80,000 g / mol, suitably 30,000-60,000 g / mol, and / or emitting fluorescence in the wavelength range of 400-520 nm under excitation from UV light.
20. The materials are: Providing a composition according to any one of claims 9 to 16, forming a dope of the composition; coagulating the fibers in a spin bath to form fibers; Recovering the fibers from the spin bath; Stretching the fiber; Washing the fibers The solidification material according to any one of claims 17 to 19, in the form of fibres obtained by
21. 21. The solidification material of claim 20, wherein the spin bath is acidic and the cellulose carbamate has a nitrogen content of 0.1 to 2% by weight.
22. The solidification material of claim 20, wherein the spin bath is alkaline and the cellulose carbamate has a nitrogen content of 0.3 to 3% by weight.
23. 20. The solidification material according to any one of claims 17 to 19, wherein the material is in the form of a film obtained by extruding cellulose carbamate in a coagulation bath to form a film.
24. A textile garment comprising a fabric, woven fabric, knitted fabric, yarn, filament yarn, textile, woven or knitted fabric, textile thread, at least a portion of which comprises a cellulose carbamate according to any one of claims 1 to 8.
25. 9. An article comprising staple fibres, flock, nonwovens, batting, weaves, tows, filament yarns, tows of filaments, at least a portion of which comprises the cellulose carbamate of any one of claims 1 to 8.
26. Use of the cellulose carbamate according to any one of claims 1 to 8 in absorbent materials, composite materials, chromatography columns, organic pigments, adhesives or microbiologically active stabilizers.
27. 1. A method for producing a cellulose carbamate polymer, comprising the steps of: mechanical pretreatment by at least grinding or chopping of at least 50 wt. % cellulose-containing waste material, including polyester, into elements having fibers with a length of 25 mm or less; an acid treatment of the mechanically treated cellulosic material; an acid treatment followed by an alkali treatment to at least partially hydrolyze the polyester; decolorization of the treated cellulosic material with ozone under alkaline conditions; and a cellulose carbamation step for forming a cellulose carbamate from the alkali-treated cellulosic material, The polydispersity index of the resulting cellulose carbamate is adjusted to 2.0-5.0 by acid treatment.